1994
DOI: 10.1002/app.1994.070530609
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of reaction of C36 dimer acids with diethylenetriamine and triethylenetetramine for reactive polyamides

Abstract: SYNOPSISKinetic studies were carried out on the reaction between dimer acids and diethylenetriamine (DETA) and triethylenetetramine (TETA) in melt phase. The reactions were performed at temperatures in the range of 145" to 190°C and followed by determination of the acid and amine values of the intermittent products. The polyamidation reactions of C36 dimer acids and DETA and TETA followed overall second-order kinetics and had activation energies of 14.4 kcal/g mol and 12.3 kcal/g mol, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Polyamides synthesized from dimer acids and mixtures of ethylenediamine and hexamethylene diamines have different results on different properties than those synthesized from single diamines (Peerman and Vertnik, 1968;Kale et al . 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Polyamides synthesized from dimer acids and mixtures of ethylenediamine and hexamethylene diamines have different results on different properties than those synthesized from single diamines (Peerman and Vertnik, 1968;Kale et al . 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In case of PMD-1, gelation was observed within 2 hr, whereas for PSD-1 and PPD-1, the product could not be precipitated. Kale et al [15] also reported gelation of the polyamide when monomers were employed in equimolar proportion.…”
Section: Resultsmentioning
confidence: 94%
“…21 Dimer acids obtained from soybean oil can be converted into both reactive and nonreactive polyamide resins. [22][23][24] The condensation of dimer acids with ethylenediamine results in nonreactive low-molecular weight polyamides. Dimer acids typically contain 10-30% trimer acids which lead to three dimensional polymers that cause stickiness, narrow melting ranges, cold flow resistance, and rheological properties useful in adhesives.…”
Section: C Fatty Acid Amidesmentioning
confidence: 99%
“…The condensation of dimer acids in slight excess of polyamines (diethylene triamine and triethylene tetramine) results in reactive polyamides resins of low molecular weight having a free amino group in the chain. 24 These are used as curing agents in epoxy resins that find application in surface coatings, adhesives, potting and casting compounds, and patching and sealing compounds. 25 Epoxy adhesives are typically two-component systems including an epoxy-resin and a polyamide curing agent.…”
Section: C Fatty Acid Amidesmentioning
confidence: 99%